PENERAPAN DATA BASE PADA UMKM ROTI BAKAR DENGAN MICROSOFT ACCESS - Salsabila Ramadhani; Wiratama, Samuel; Alycia Putri; Sekar Laksita Gayatri; Cristin Simanjuntak; Putri Haya Azzahra; Adisya Fauziah Jazmine Daulay; Suhendi Irawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (UMKM) are a sector that contributes significantly to the national economy. However, many UMKM actors still manage business information manually, especially in recording sales data, inventory, and daily transactions. This traditional recording method often causes various problems, such as a high risk of data entry errors, the possibility of losing archives, and difficulties in searching for information when needed. These obstacles can reduce operational effectiveness and potentially hinder business growth in the long term. Based on these conditions, this study was conducted with the aim of implementing a database system for a Toast Bread UMKM using Microsoft Access. The application of this system is expected to provide a more efficient, organized, and easily accessible alternative for data management whenever needed. To collect the data, the researcher conducted direct interviews with Toast Bread vendors operating around the Vocational School of IPB University. From the interview process, important information needed by the vendors was identified, such as raw material stock data, menu lists, sales frequency, and daily report requirements. The findings of this study show that the use of a Microsoft Access-based database provides positive impacts for UMKM. The system helps simplify data storage and processing, as well as produce faster and more accurate reports. In addition, more structured data access also helps UMKM actors make business decisions more precisely. Overall, the implementation of Microsoft Access has proven to increase efficiency, accuracy, and professionalism in data management for the Toast Bread UMKM, thus supporting the business to grow in a more organized and sustainable way.